Conserved noncoding genomic sequences associated with a flowering-time quantitative trait locus in maize - Salvi, Silvio; Sponza, Giorgio; Morgante, Michele; Tomes, Dwight; Niu, Xiaomu; Fengler, Kevin A; Meeley, Robert; Ananiev, Evgueni V; Svitashev, Sergei; Bruggemann, Edward; Li, Bailin; Hainey, Christine F; et al. (Proceedings of the National Academy of Sciences - PNAS, 2007)
Flowering time is a fundamental trait of maize adaptation to different agricultural environments. Although a large body of information is available on the map position of quantitative trait loci for flowering time, little is known about the molecular basis of quantitative trait loci. Through positional cloning and association mapping, we resolved the major flowering-time quantitative trait locus, Vegetative to generative transition 1 (Vgt1), to an [almost equal to]2-kb noncoding region positioned 70 kb upstream of an Ap2-like transcription factor that we have shown to be involved in flowering-time control. Vgt1 functions as a cis-acting regulatory element as indicated by the correlation of the Vgt1 alleles with the transcript expression levels of the downstream gene. Additionally, within Vgt1, we identified evolutionarily conserved noncoding sequences across the maize-sorghum-rice lineages. Our results support the notion that changes in distant cis-acting regulatory regions are a key component of plant genetic adaptation throughout breeding and evolution.